Kārvān-i ḵẖayāl : majmūʻah-yi ḵẖut̤ūt̤, 4 Sitambar 1940-12 Nombar 1946 - Āzād, Abūlkalām, 1888-1958 (SAMP early 20th-century Indian books project ;, 1946)
Collection of letters written by Abūlkalām Āzād, 1888-1958, Indian statesman and Ḥabīburraḥmān Ḵẖā̄ṉ Shervānī, Indian politician.